El efecto de las patentes en la innovación ambiental: Balances y retos (2020)
The article seeks to highlight the role acquired by patents in the field of inventions and utility models that can be considered environmental innovations. Its objective is to characterize the key role that they have had through new products, processes and services that provide solutions of sustainability, generate positive impacts to the environment or mitigate negative effects derived from those activities that contribute to the current conditions of environmental deterioration of the planet. Through a deductive methodological approach, the authors start from general notions about intellectual property, environment and development, in order to arrive at their own reflections as findings, and to place pat- ents on environmental innovations as a key link in favor of the environment, thus showing how, in effect, patents have managed to contribute to the improvement of environmental conditions, helping the State and companies to comply with their environmental commit- ments to society.